Rancang Bangun View controller Menggunakan Sensor Akselerometer Pada Game Bus Simulator Sebagai Sarana User Experience (UX) Berbasis Sistem Embedded - Bukhori Darmawan; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
games with a different experience or could be said to feel the experience in playing the game.-Racing game on an awful lot of opportunities to apply user experience, on this occasion the researchers to develop a system to replace a mouse in-game play racing.Based on that required a system view controller, system implementation view controller is done with the arduino pro micro as mikorkontroler and MP9250 as input motion sensors are then connected to a laptop with media communications either a serial cable and installed on the user's head with a headband are embedded.To generate a different user experience in playing a game, the system is able to restrict the movement of the view controller with 40 Â° restrictions to the movement of the user's head on when turned to the right and to the left so the user can freely when turned to the right and to the the left will be used.The system will be tested in its entirety from some corners that will result in the value of the angle with the value of the difference in average low RMSE where the system can already be used and tested by quantitative descriptive survey method of correspondence for 30 get the category values from the user experience.The results of the test are obtained by averaging the test angle sensor is approximately 0.2 Â° and the corresponding user experience testing results systems were able to get a good category average based on feedback given by 30 users.